Dynamic changes of the proportion of HLA-DR and CD38 coexpression subsets on T lymphocytes during IFN-based chronic hepatitis B treatment - Lin, Yanjie; Shen, Ge; Xie, Si; Bi, Xiaoyue; Lu, Huihui; Yang, Liu; Jiang, Tingting; Deng, Wen; Wang, Shiyu; Zhang, Lu; Lu, Yao; Gao, Yuanjiao; et al. (Frontiers in Immunology, 2023)
Background To investigate the changes of human leukocyte antigen DR (HLA-DR) and CD38 coexpression subsets on T lymphocytes following interferon (IFN) therapy for those who have chronic hepatitis B (CHB). Methods A prospective cohort of CHB patients participated in this study. CHB patients without IFN treatment (including naïve and nucleoside [nucleotide] analogs [NAs]-treated patients) were given pegylated interferon alfa (Peg-IFNα) treatment. Peripheral blood samples were taken at baseline, 4 weeks and 12-24 weeks of Peg-IFNα treatment. For the patients who entered the Peg-IFNα plateau phase due to the stagnation of the decrease in HBsAg, and Peg-IFNα was discontinued and Peg-IFNα therapy was resumed after an interval of 12-24 weeks. During the interval, they received first-line NAs treatment. Peripheral blood samples were collected at the baseline of the plateau phase, 12-24 weeks of intermittent treatment, and 12-24 weeks of Peg-IFNα retreatment. The peripheral blood samples were taken to determine virological, serological and biochemical indices of hepatitis B virus (HBV), and T lymphocyte related phenotypes were detected using flow cytometry. Results In the process of long-term treatment of Peg-IFNα, the percentage of HLA-DR+CD38dim subsets increased significantly at first, then decreased gradually, while the percentage of HLA-DR+CD38hi subsets markedly increased. During long-term Peg-IFNα treatment, there was a considerable negative correlation between HBsAg and the HLA-DR+CD38hi subset percentage. The persistent high proportion of HLA-DR+CD38hi subsets was related to the occurrence of Peg-IFNα plateau phase. After Peg-IFNα intermittent treatment, the percentage of HLA-DR+CD38hi subsets decreased significantly. After Peg-IFNα retreatment, the level of HBsAg began to decrease again. At the same time, the percentage of HLA-DR+CD38hi subsets significantly increased, but it was still lower than that at the baseline level. Conclusions The spectrum of HLA-DR and CD38 coexpression subsets on T lymphocytes changed during the long-term treatment of IFN. The establishment of the IFN plateau phase was linked to the persistence of a considerable proportion of HLA-DR+CD38hi subsets on T lymphocytes. IFN intermittent treatment could significantly reduce the proportion of HLA-DR+CD38hi subsets, helping regain the antiviral efficacy of IFN during IFN retreatment.